BEHAVIORAL INSIGHT FOR COVID-19 AMONG STAFFS OF A TEACHING HOSPITAL IN KUMAUN REGION, UTTARAKHAND - Mohd Maroof; Sadhana Awasthi; Thakkar Hemben Kanubhai; Maneesh Bhatt; Gaihemlung Pamei; Rupali Gupta (Universitas Airlangga, 2022)
Introduction: COVID-19 is caused by a novel virus and is known to be an infectious respiratory disease affecting more than 200 countries and union territories of the world. 80% of the patients are shown to have mild to moderate disease. Illness prevention is the mainstay of getting away from the condition with the non-availability of vaccines or medicine. Methods: The aim & objective of this study is to describe the behavioral insight (knowledge, attitude & practice) regarding preventive measures of COVID-19 among the teaching hospital staff. An institutional-based descriptive study was conducted among 168 staff, including lab technicians, doctors, staff nurses, and other supporting staff of a tertiary hospital using a convenient sampling technique. The data were obtained by interviewing staff with a pre-tested semi-structured schedule. Result: The study results showed that most of the respondents were found to have good knowledge, attitude, and practice towards preventive measures such as social distancing, hand hygiene, face mask, and PPE Kit. 88% of participants were using 3 layered medical masks, and most of them (63%) were using a regular wash of face mask. Among most respondents, no gap between knowledge and practice was seen; however, proper use, handling, and disposal of face masks and other PPE was a concern. Conclusion: Therefore, there is a need to improve the knowledge of COVID-19 among healthcare workers, which is possible with the availability of good quality Information Education and Communication (IEC) materials. Keywords: Behavioral insight, COVID-19, Social Distancing, Face mask, Hand Hygiene, PPE